EMPOWER Curriculum: Teaching Effective Use of Community Resources for Children With Special Health Care Needs - Marie Clark; Wendy Hobson-Rohrer; Blanche Benenson; Ruth Stein (MedEdPORTAL, 2015)
Abstract Introduction Children and youth with special health care needs (CYSHCN) are a unique population of patients, whose care often requires coordination of community resources. Intended to empower providers to connect families with effective community resources, the EMPOWER curriculum was implemented by a third-year fellow in developmental-behavioral pediatrics rotation to help their pediatric resident colleagues. Methods EMPOWER is an experiential curriculum intended for residents or medical students with an interest in primary care or chronic care. The curriculum is divided into three sessions with an interim problem-based learning (PBL) activity. The first seminar focuses on developing an understanding of life course theory. The second seminar introduces skills in needs assessment and strategies to locate and perform a quality assessment of community resources. The PBL assignment allows learners to practice the skills learned in the previous two seminars with a family. The third session involves a review of the PBL assignment and mapping of selected resources identified through the learners' assignments, by visiting the resources within the community. A preliminary convenience sample evaluation of the impact of the curriculum on our learners was completed during 2013-2014 academic year using a de-novo pre-/posttest to assess self-report of knowledge, comfort level, and behavior. Unique identifying numbers were assigned to the surveys to preserve anonymity and enable comparison of pre-/posttest responses using McNemar's test of paired proportions. Results The EMPOWER curriculum has been implemented successfully for five cycles of resident rotators. Following the intervention, significantly higher proportions of residents reported feeling knowledgeable about CYSHCN (50% vs. 89%, p = < .01), said they would ask about community resources (25% vs. 54%, p = .04), and check resource quality (4% vs. 29%, p = .02). In addition, higher proportions were comfortable discussing income, personal safety, housing, organizations, transition, and respite. Discussion In summary, findings suggested positive effects of participation in the EMPOWER curriculum. Thus, it may be a useful tool to teach pediatric residents about coordination of community resources for children and youth with special health care needs.